Extreme weather and financial markets opportunities in commodities and futures - Oxley, Lawrence J., 1969- (Wiley trading ;, 2012)
"The positive effects of climate change on the market. Record-setting snowfall, cyclones in Australia, chronic drought in Russia, and other dramatic weather events are getting increased attention from scientists and the general public. The effects of climate change present challenges to many sectors, but also present major investing opportunities in the stock, bond, and futures markets. Extreme Weather and The Financial Markets looks at climate change from an investor's standpoint. The climate change debate is somewhat irrelevant to those in the financial industry, since we already live with more than enough extreme climate events to impact the financial markets. To the extent that environmental scientists are correct and global climate change is real and getting worse, the more investment opportunities we have The book presents investment ideas that will work under today's global climate condition and will become even more lucrative if global climate change continues Written by Larry Oxley, an acclaimed author who has personally outperformed the index in the Basic Materials sectors (i.e. chemicals, metals, mining, and forest products) for each of the last five years--in both good and bad markets and throughout the global recession--in a portfolio of nearly $2 billion Focusing on the investment opportunities during dramatic weather events, Extreme Weather and The Financial Markets offers advice on how to capitalize on global climate change"--